Issues of Food Pricing Policy in Pakistan and the Way Forward (The Pakistan Development Review, 2025)
Price control policies are implemented to support farmers and ensure affordability for consumers but often lead to market distortions and inefficiencies. The present study aims to investigate the role of food pricing policy in Pakistan. In each district, on the behalf of Deputy Commissioner Office (DCO), market committees (MC) fix retail prices of fruits and vegetables daily. We collected data on 11 fruits and vegetables from four mega cities (Islamabad/ Rawalpindi, Lahore, Faisalabad, and Multan) for 10 consecutive days. It is observed that the difference between farm gate prices and DCO prices varies between 6.2 percent to 20.3 percent which is not insufficient to cover the different costs (transportation cost from mandi to retail shop, losses of wastage, opportunity cost of the retailers’ labour and profit margins) of retailers. Our comparison of prevailing retail prices with the retail prices reported by PBS further demonstrates that PBS under-reported the retail prices to curb the inflationary effect.The government procures 70-80 percent of the market surplus to maintain prices close to the minimum support price (MSP) and the government is spending about Rs.130 billion each year to achieve this single objective. However, retail prices increase more than double that of MSP and the benefit of the increase in prices goes to flour mills and traders. Our analysis for the year 2021-22 reveals that government footprints in wheat marketing are equal to Rs. 131 billion. If this cost had been passed on to the consumers in the form of increased prices (under the assumption that procuring, and handling will take place under the private sector), then it would have increased the retail prices by 28 percent. Hence, retail prices would be Rs. 70.3/kg in contrast to the government’s desired price of Rs. 55/kg (MSP). If we add up another additional profit of Rs.10/kg to incentivise the private sector, then prices will increase to Rs. 80.3/kg but the wheat prices will increase to Rs.110/kg. This implies that an extra profit of Rs. 30/kg is earned by the flour mills and other value chain actors. This could be diverted to consumers by adopting a free market mechanism. In case of wheat shortage, the retail price of imported wheat in the private sector would be Rs.94.3/kg (after adding transportation cost, loading, and unloading charges, and Rs.10/kg profit in the private sector) which is still lower than retail price of Rs.110/kg during 2021-22. Based on the study’s findings, it is recommended that the government need to minimise its footprints and allow market forces to determine retail prices. However, it should continue to play its regulatory role to assure equal access to all actors in the market to ensure fair market practices.